2013
DOI: 10.1371/journal.pone.0084646
|View full text |Cite|
|
Sign up to set email alerts
|

Using Expression Profiling to Understand the Effects of Chronic Cadmium Exposure on MCF-7 Breast Cancer Cells

Abstract: Cadmium is a metalloestrogen known to activate the estrogen receptor and promote breast cancer cell growth. Previous studies have implicated cadmium in the development of more malignant tumors; however the molecular mechanisms behind this cadmium-induced malignancy remain elusive. Using clonal cell lines derived from exposing breast cancer cells to cadmium for over 6 months (MCF-7-Cd4, -Cd6, -Cd7, -Cd8 and -Cd12), this study aims to identify gene expression signatures associated with chronic cadmium exposure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
2
14
1
Order By: Relevance
“…While our data suggest a positive correlation between cadmium exposure and the expression of these proteins, it is likely other ubiquitinationassociated proteins involved in the ubiquitination pathways are also affected by cadmium. In support of this, our recent microarray analysis identified multiple ubiquitination-associated genes deregulated in five different breast cancer clonal cell lines chronically exposed to cadmium (Table S1) [46]. The results from this study along with indications from the microarray analysis warrant further studies to examine the role of cadmium in protein stability.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…While our data suggest a positive correlation between cadmium exposure and the expression of these proteins, it is likely other ubiquitinationassociated proteins involved in the ubiquitination pathways are also affected by cadmium. In support of this, our recent microarray analysis identified multiple ubiquitination-associated genes deregulated in five different breast cancer clonal cell lines chronically exposed to cadmium (Table S1) [46]. The results from this study along with indications from the microarray analysis warrant further studies to examine the role of cadmium in protein stability.…”
Section: Discussionsupporting
confidence: 67%
“…Future research aimed at dissecting the role of ERα in cadmium‐induced E‐cadherin ubiquitination may offer further insights into how this heavy metal contributes to breast cancer progression. In addition, it would be worth investigating whether or not chronic cadmium exposure promotes epithelial mesenchymal transition (EMT), particularly in light of our recent microarray analysis study , which does indicate that multiple genes associated with EMT are deregulated in the presence of cadmium ().…”
Section: Discussionmentioning
confidence: 99%
“…Li et al ( 40 ) noted that PRSS30P is upregulated in lung adenocarcinoma. SCARNA9 is observed to be overexpressed in breast cancer cells on exposure to cadmium ( 41 ). However, ARHGAP5-AS1 and MCF2L-AS1 are rarely studied in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the widespread use of cadmium, gastrointestinal absorption of cadmium without being aware is unavoidable. Several studies about carcinogenic effects of cadmium have been published and the cytotoxic action and carcinogenesis of cadmium in many organs, especially the lung, liver, breast, and kidney, are well known (16)(17)(18). However, the mechanisms underlying cadmium-induced carcinogenesis have remained largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mukhin et al (26) suggested a simple model for ERK-1/2 activation by ROS (NAD(P)H oxidase → Giβγ → Src → ERK-1/2 pathway) using CHO cells. Concurrent inhibition of tyrosine phosphatase (PTPase) by ROS has been suggested to be another mechanism of ERK-1/2 activation (18). Because all PTPases have a conserved cysteine residue in their catalytic domain, the inhibition of PTPase activity by ROS may account for activation of ERK-1/2 by ROS.…”
Section: Discussionmentioning
confidence: 99%